2015
DOI: 10.1093/jnci/djv341
|View full text |Cite
|
Sign up to set email alerts
|

Fine Particle Pollution, Alanine Transaminase, and Liver Cancer: A Taiwanese Prospective Cohort Study (REVEAL-HBV)

Abstract: Long-term PM2.5 exposure increased the risk for liver cancer, and chronic inflammation of the liver may underlie the pathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
100
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(111 citation statements)
references
References 41 publications
6
100
5
Order By: Relevance
“…Only PM 2.5 was positively associated with GGT (5.1% increase (95% CI: 0.1% to 10.4%) per 2.8 µg/m 3 increment in annual average PM 2.5 ) and no significant associations were found for other air pollutants or liver enzymes 24. A Taiwanese study found long-term exposure to PM 2.5 was positively associated with ALT levels (44.17% increase (95% CI: 23.21% to 68.68%) per 12.2 µg/m 3 PM 2.5 increment) and the ALT significantly mediated the association between PM 2.5 and incident hepatocellular carcinoma observed in this study 17. A recent study among 74 American children found that traffic-related air pollution was not associated with AST or ALT, but associated with cytokeratin-18, a marker of hepatocellular apoptosis 25.…”
Section: Discussioncontrasting
confidence: 74%
“…Only PM 2.5 was positively associated with GGT (5.1% increase (95% CI: 0.1% to 10.4%) per 2.8 µg/m 3 increment in annual average PM 2.5 ) and no significant associations were found for other air pollutants or liver enzymes 24. A Taiwanese study found long-term exposure to PM 2.5 was positively associated with ALT levels (44.17% increase (95% CI: 23.21% to 68.68%) per 12.2 µg/m 3 PM 2.5 increment) and the ALT significantly mediated the association between PM 2.5 and incident hepatocellular carcinoma observed in this study 17. A recent study among 74 American children found that traffic-related air pollution was not associated with AST or ALT, but associated with cytokeratin-18, a marker of hepatocellular apoptosis 25.…”
Section: Discussioncontrasting
confidence: 74%
“…PM 2.5 induced the metastatic capabilities of lung cancer, including migration and invasion (11). The patient observational reports indicated that PM 2.5 exposure was associated with HCC via chronic liver inflammation (12). The incidence of HCC may also be associated with PM 2.5 , therefore the effects of PM 2.5 on HCC cells require further study.…”
Section: Introductionmentioning
confidence: 99%
“…The liver may be a target as pm 2.5 can induce oxidative stress, inflammation, genotoxicity, and accelerate liver inflammation and steatosis, driving the development and progression of liver cancer . For example, pm 2.5 exposure has been linked to increased serum levels of hepatic enzymes such as alanine aminotransferase, which is a marker of liver damage and a predictor of hepatocellular carcinoma (HCC), the most common liver cancer . Long‐term pm 2.5 exposures have recently been linked to an increased incidence of HCC, but the effects of pm 2.5 exposure on survival of HCC have not been investigated.…”
mentioning
confidence: 99%
“…For example, pm 2.5 exposure has been linked to increased serum levels of hepatic enzymes such as alanine aminotransferase, which is a marker of liver damage and a predictor of hepatocellular carcinoma (HCC), the most common liver cancer . Long‐term pm 2.5 exposures have recently been linked to an increased incidence of HCC, but the effects of pm 2.5 exposure on survival of HCC have not been investigated. We hypothesized that pm 2.5 exposure accelerates the progression of HCC and decreases survival after the diagnosis of liver cancer.…”
mentioning
confidence: 99%